Acute myopericarditis caused by Micoplasma pneumonae in a 5 years old child - Condori Alvino, Karen (2021)
Infections caused by Mycoplasma pneumoniae are well recognized all over the world, and this microorganism is a common pathogen affecting the lower respiratory tract. Acute pericarditis is often accompanied by myocarditis, and both conditions coexist in clinical practice because they have common etiologic agents, mainly cardiotropic viruses. We present a very unusual case of myopericarditis caused by Mycoplasma pneumoniae affecting a 5 year-old child, who developed an interesting clinical outcome.